2005
DOI: 10.1038/modpathol.3800405
|View full text |Cite
|
Sign up to set email alerts
|

Maximum tumor diameter is an independent predictor of prostate-specific antigen recurrence in prostate cancer

Abstract: Maximum tumor diameter has been shown to correlate with multiple predictors of clinical outcome in prostate cancer. In the current study, we prospectively analyze whether maximum tumor diameter is a significant predictor of prostate-specific antigen (PSA) recurrence. The study population consisted of 364 patients who underwent radical prostatectomy for prostate cancer. Prostatectomy specimens were evaluated by wholemount processing of the entire prostate. Maximum tumor diameter was measured from the whole-moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 24 publications
2
61
0
2
Order By: Relevance
“…The discrepancy may be explained by the difference of the cohorts. A large median MTD of 15 mm in our study sample might have caused misleading statistical significance due to biased patient selection, although there was no discernible tendency suggesting that the analysis of samples with larger tumors resulted in or against favor of MTD as the predictor in the previous reports 8, [17][18][19][20][21][22] . For this possibility, we analyzed a cohort of smaller MTD (n ¼ 334, 0.9-30 mm), confirming MTD predicting PSA recurrence H Fukuhara et al that MTD was still a significant factor for the time to BCR in this cohort in multivariate analysis (P ¼ 0.023).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The discrepancy may be explained by the difference of the cohorts. A large median MTD of 15 mm in our study sample might have caused misleading statistical significance due to biased patient selection, although there was no discernible tendency suggesting that the analysis of samples with larger tumors resulted in or against favor of MTD as the predictor in the previous reports 8, [17][18][19][20][21][22] . For this possibility, we analyzed a cohort of smaller MTD (n ¼ 334, 0.9-30 mm), confirming MTD predicting PSA recurrence H Fukuhara et al that MTD was still a significant factor for the time to BCR in this cohort in multivariate analysis (P ¼ 0.023).…”
Section: Discussionmentioning
confidence: 52%
“…According to these results, the analysis was performed between 420 and p20 mm of MTD in our study. Eichelberger et al 19,20 confirmed the positive correlation between MTD and the risk of BCR in their study of 364 men; increased MTD was associated with shorter time to BCR (P ¼ 0.01) after controlling for risk factors, such as Gleason's score and surgical margins in Cox multiple regression models. They also found that MTD was significantly correlated with pre-operative PSA levels, prostate weight, TTV, Gleason's score and pathological stage.…”
Section: Discussionmentioning
confidence: 81%
“…15,16,[20][21][22] Our observations on radical prostatectomy specimens removed for carcinoma with positive preoperative uPM3 testing indicate that uPM3 is a significant and independent biomarker that detects prostate cancers of similar volume, location, extent and grade as other tests for early detection. uPM3 does not preferentially identify large or aggressive prostate cancers.…”
Section: Discussionmentioning
confidence: 71%
“…33 Although the prognostic significance of quantitation of prostate cancer volume and the proportion of prostate gland tissue involved by carcinoma is not disputed, few studies are able to provide evidence that parameters reflecting prostate cancer volume are of significance, independent of Gleason score, pathological stage and surgical margin status. [34][35][36][37] The study by Stamey et al 34 was undertaken on a series of prostatectomy specimens that antedated the PSA screening era, and for this reason tumors in this series were much more advanced than those currently identified in the current era of patient and physician directed screening. More recently Eichelberger et al 37 did demonstrate that measurement of the maximum diameter of the dominant tumor has independent prognostic value.…”
Section: Technical Aspects Of Pt2 Substagingmentioning
confidence: 99%
“…36 Authors of several landmark studies 34,35,37,50 have put forward that measurement of size or volume may be limited to assessment of the largest tumor nodule in a prostatectomy specimen and a method that may be appropriate is measurement of the maximum diameter of the largest tumor nodule in the transverse plane, after delineating the edges of the tumor on the glass slide. 56 Potential complications for absolute measurement of tumor diameter in volume may arise when (1) the tumor extends beyond the glass slide; (2) the prostate is not fully embedded; (3) tissue blocks are cut at irregular intervals; and (4) shrinkage of tissue occurs due to processing, which may vary between laboratories.…”
Section: Measurement Of Tumor Volumementioning
confidence: 99%